2020
DOI: 10.1038/s41598-020-68778-6
|View full text |Cite
|
Sign up to set email alerts
|

Fermented soybean meal affects the ruminal fermentation and the abundance of selected bacterial species in Holstein calves: a multilevel analysis

Abstract: The effect of soybean meal (SBM) replacement with fermented SBM (FSBM) on ruminal fermentation and bacterial abundance in Holstein calves was investigated in this study. Thirty nine calves were randomized to: (1) control: 27% SBM + 0% FSBM (FSBM0, n = 13); (2) 18% SBM + 9% FSBM (FSBM9, n = 13); and (3) 13.5% SBM + 13.5% FSBM (FSBM13, n = 13). SBM contained a greater amount of large peptides containing 3 to 10 amino acids (AAs), while FSBM had a greater amount of ammonia nitrogen (NH 3-N), free AAs, and small p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 62 publications
2
19
0
Order By: Relevance
“…As was revealed in the results of the current trial, replacing SBM with FSBM significantly decreased the TVFA concentration and the molar ratio of butyrate, while tended to reduce the acetate molar proportion. Similarly, Feizi et al (2020) found that the substitution of FSBM for SBM at 30 and 50% both significantly lowered the molar ratio of acetate in the rumen fluid of Holstein calves, while the molar proportion of butyrate tended to be less in the calves fed the starter in which SBM was replaced by FSBM at 30%. This phenomenon could be explained by the greater quantity of RUP in FSBM (Stein et al, 2008;Rezazadeh et al, 2019), as it has been reported that the TVFA production and the molar percentages of acetate and butyrate was lessened in response to the existence of RUP in a dual-flow continuous culture system using rumen contents obtained from Holstein cattle (Griswold et al, 1996).…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…As was revealed in the results of the current trial, replacing SBM with FSBM significantly decreased the TVFA concentration and the molar ratio of butyrate, while tended to reduce the acetate molar proportion. Similarly, Feizi et al (2020) found that the substitution of FSBM for SBM at 30 and 50% both significantly lowered the molar ratio of acetate in the rumen fluid of Holstein calves, while the molar proportion of butyrate tended to be less in the calves fed the starter in which SBM was replaced by FSBM at 30%. This phenomenon could be explained by the greater quantity of RUP in FSBM (Stein et al, 2008;Rezazadeh et al, 2019), as it has been reported that the TVFA production and the molar percentages of acetate and butyrate was lessened in response to the existence of RUP in a dual-flow continuous culture system using rumen contents obtained from Holstein cattle (Griswold et al, 1996).…”
Section: Discussionmentioning
confidence: 79%
“…In the current study, results showed that entirely replacing SBM with FSBM in the diet for lactating Holstein dairy cows did not affect the ruminal pH or the NH 3 -N concentration. However, Feizi et al (2020) concluded that the substitution of FSBM for SBM at 50% in the starter diet raised the level of NH 3 -N in the rumen fluid of Holstein calves in a previous study, in which the ruminal pH was not measured. This inconsistency can be attributed to the differences in the animals, composition of experimental rations, and contents of FSBMs, and further research is required.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations